2017
DOI: 10.2174/1874325001711011094
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric Anatomical Study of Sural Nerve: Where is The Safe Area for Endoscopic Gastrocnemius Recession?

Abstract: Purpose:To ascertain in cadavers where the sural nerve crosses the gastro-soleus complex and where the gastrocnemius tendon merges with the Achilles tendon in relation to the calcaneal tuberosities.Methods:Twelve cadaveric lower limbs (6 right and 6 left) were dissected. The distances between the calcaneal tuberosities and the lateral border of the Achilles tendon where the sural nerve crosses from medial to lateral, as well as to the gastrocnemius tendon insertion into the Achilles tendon, were measured.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Other anatomical studies published in 2007 and 2008 by Blitz et al showed the high variability of the location of the fusion of the two aponeuroses (conjoint junction) [ 7 , 8 ], leading the Strayer technique to a possible aspecific aponeurosis release of both the gastrocnemius and of the soleus aponeurosis, theoretically producing the risk of a complete detachment of the gastrocnemius with the risk of a complete consequent muscular atrophy and loss of function [ 7 , 8 ]. Moreover, during the Strayer procedure all surgical instruments are far between the sural nerve and his accompanying lesser saphenous vein, existing in tremendous anatomical variations [ 23 , 28 ], enhancing the risk of neurovascular injuries [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other anatomical studies published in 2007 and 2008 by Blitz et al showed the high variability of the location of the fusion of the two aponeuroses (conjoint junction) [ 7 , 8 ], leading the Strayer technique to a possible aspecific aponeurosis release of both the gastrocnemius and of the soleus aponeurosis, theoretically producing the risk of a complete detachment of the gastrocnemius with the risk of a complete consequent muscular atrophy and loss of function [ 7 , 8 ]. Moreover, during the Strayer procedure all surgical instruments are far between the sural nerve and his accompanying lesser saphenous vein, existing in tremendous anatomical variations [ 23 , 28 ], enhancing the risk of neurovascular injuries [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, either for the open and the endoscopic GIAR procedure there have been described some saphenous nerve and/or great saphenous vein damages despite their constant anatomy, leading to complications [ 28 ]. Performing the endoscopic GIAR in obese patients showed that in some cases the interval between the gastrocnemius and soleus muscles is difficult to identify, leading the surgeon to widen the portal to ensure the correct surgical spot, losing the “minimally invasive” intention [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 The site where the sural nerve courses laterally at the mid-fibula level is approximately 10 cm proximal to the calcaneal tuberosity. 39 Hoefnagels et al propose to do the gastrocnemius recession proximally as the sural nerve is protected by the lateral head of gastrocnemius muscle. 31 Nonetheless, injury to the sural nerve is still possible due to the transverse incision made for gastrocnemius recession.…”
Section: Novel Technique Of Gastrocnemius Recessionmentioning
confidence: 99%
“…Endoscopic gastrocnemius recession appears to be less invasive and may have advantages over open procedures in terms of skin damage, smaller incisions, shorter recovery times, fewer complications, and reduced morbidity [28], although sural nerve injury and the need for limb exsanguination may be limitations [29].…”
Section: Introductionmentioning
confidence: 99%